Knowledge and attitude of mothers regarding feeding practices among children of 6 months to 2 years of age visiting a tertiary care centre of Ahmedabad, Gujarat, India - Parikh, Rutvik H.; Tolani, Jayshree N.; Shah, Nitinkumar D. (International Journal of Contemporary Pediatrics, 2019)
Background: India is facing a grave challenge of having very high rates of child under-nutrition and a high infant and child mortality, which demands an urgent need for comprehensive multi-pronged evidence based strategy to tackle the situation. Breastfeeding offers the ultimate food during the first 6 months of life. Complementary feeding starts when breast milk is no longer sufficient by itself, the target age is between 6-24 months. Complementary feeding plays critical role in bridging these gaps between nutritional requirements and growth and development of child with increasing age. Complementary feeding strategies encompass a wide variety of interventions designed to improve not only the quality and quantity of these foods but also improve the feeding behaviors. In this review we analyzed knowledge and attitude of mother regarding feeding practices among children of 6 months to 2 years of age who had visited tertiary care centre. Methods: Personal interview of mothers having a child in the age group of 6 months to 2 years of age in the duration of October 2017 to March 2018 visiting pediatric department at a tertiary care centre and willing to give information are included in the sample. The Questions regarding socio demographic profile, various occupations, type of feeding practiced, knowledge regarding feeding and complimentary feeding were included in Performa. Data was entered in MS Excel and analyzed using SPSS software. Results: Almost 8 out of 10 mothers were literate in the study (77.80%). About 75% mothers didn’t know the correct type of complimentary feeding to initiate for their babies. Knowledge about correct time of starting complimentary feeding was more commonly found in housewife mothers than the working mothers and findings was supported by statistical significance. Mothers with >=2 children were using correct type of food for complementary feeding more commonly that with mothers having single child. Conclusions: The present study highlighting knowledge gap and practice gap in mothers about complimentary feedings. Appropriate complementary feeding education emphasizing timely initiation and meal diversity is necessary to improve knowledge and feeding practices of mothers whether mother is educated or uneducated.